Research on Probability Estimation Method of Investment Cost of Water Conservancy Construction Project - Feng, Jiandong (Transactions on Economics, Business and Management Research, 2024)
The construction period of water conservancy construction project is long, and the project cost is affected by many uncertain factors. There is a great difference between the final account value after the completion of the project and the budget value before the commencement.Therefore, this paper considers the complexity and variability of the project cost, analyzes and constructs the probability estimation theory of investment cost from the perspective of system analysis, and applies it to the estimation of the investment cost of the construction project of Matan River miaotazi hydropower station, and calculates the probability distribution of the total cost change.The research results can provide a new idea for the estimation of investment cost of water conservancy projects, and also provide valuable reference for the estimation of investment cost of Matan River miaotazi hydropower station.